Extracting Hidden Data from Encrypted Images Using IWT - Shelake, Nitin; Durugkar, SR (International Journal of Computer Sciences and Engineering, 2015)
Reversible data hiding technique in which the hidden data property is maintained even after processing on the image. The original cover image remains same after processing on the embedded image, original data is obtained. The image is used to embed additional information in the encrypted images, applies in many fields of security which can be recoverable with original media and the hided data without loss. Some previous methods embed data reversible vacating room from the encrypted images, which matter to error on data extraction and/or image restoration. This system proposes a reversible data hiding technique which work is separable; the receiver can extract embedded data. If a system for lossless compression of images applies a recover step, this step must map integer input values to integer output values. This can be achieved using the integer wavelet transform. This proposed system can achieve the excellent reversibility, that is, data extraction and same image quality. This system is better to handle secret communication in open environment like internet